Current perspectives on the management of patients with advanced RET-driven thyroid cancer in Europe - Elisei, Rossella; Grande, Enrique; Kreissl, Michael C.; Leboulleux, Sophie; Puri, Tarun; Fasnacht, Nicolas; Capdevila, Jaume (Frontiers in Oncology, 2023)
The incidence of thyroid cancer is increasing worldwide with the disease burden in Europe second only to that in Asia. In the last several decades, molecular pathways central to the pathogenesis of thyroid cancer have revealed a spectrum of targetable kinases/kinase receptors and oncogenic drivers characteristic of each histologic subtype, such as differentiated thyroid cancer, including papillary, follicular, and medullary thyroid cancer. Oncogenic alterations identified include B-Raf proto-oncogene (BRAF) fusions and mutations, neurotrophic tyrosine receptor kinase (NTRK) gene fusions, and rearranged during transfection (RET) receptor tyrosine kinase fusion and mutations. Multikinase inhibitors (MKIs) targeting RET in addition to multiple other kinases, such as sorafenib, lenvatinib and cabozantinib, have shown favourable activity in advanced radioiodine-refractory differentiated thyroid cancer or RET-altered medullary thyroid cancer; however, the clinical utility of MKI RET inhibition is limited by off-target toxicity resulting in high rates of dose reduction and drug discontinuation. Newer and selective RET inhibitors, selpercatinib and pralsetinib, have demonstrated potent efficacy and favourable toxicity profiles in clinical trials in the treatment of RET-driven advanced thyroid cancer and are now a therapeutic option in some clinical settings. Importantly, the optimal benefits of available specific targeted treatments for advanced RET-driven thyroid cancer require genetic testing. Prior to the initiation of systemic therapy, and in treatment-naïve patients, RET inhibitors should be offered as first-line therapy if a RET alteration is found, supported by a multidisciplinary team approach.